Epidemiological and clinical characterization of a population-based cohort of cutaneous malignant melanoma patients in the South Region of Portugal - Filipa Alves da Costa; Adriana Ramos; Catarina Bernardo; Fábio Cardoso Borges; Ana Costa Miranda; the ROR-Sul network (Scientific Reports, 2023)
Abstract An historical population-based cohort study was conducted aiming to estimate the incidence of cutaneous malignant melanoma in the South Region of Portugal between Jan 2016 and June 2017; to clinically characterize the diagnosed individuals; to describe instituted treatment; and to estimate survival outcomes. Data were extracted from a cancer registry (ROR-Sul) covering 4,800,000 inhabitants (46% of the Portuguese population) and included a total of 789 individuals meeting eligibility criteria. The crude incidence rate (18 months) of melanoma was 13.36/100,000 inhabitants and the Age-Standardized Incidence Rate per 100,000 World population was 9.65/100,000 inhabitants. The most common histological subtypes identified were superficial extension, followed by malignant melanoma and nodular melanoma. Most cases were diagnosed in stage I (50.39%), equally distributed by sex and with a median age of 65 years. During the study period, 174 recurrence events were recorded (23.45%) and recurrence-free survival rate was significantly lower in more advanced stages. Patients had a two-fold risk of recurrence/death when in presence of ulcerated tumors [adjusted hazard ratio (adj HR) = 2.28; 95% confidence interval (CI) 1.40–3.70]. Overall survival rate at 3-years was 80.54% (95% CI 77.58–83.15), higher than previous national reports, and considerably higher for individuals diagnosed at earlier stages (p < 0.001). We have also identified differential survival outcomes in stages II–III explained by the uptake of sentinel lymph node biopsy. The epidemiologic and clinical characteristics of malignant melanoma patients studied are consistent with international literature. The incidence and rates observed suggests additional public health campaigns are needed to modify behaviours of the Portuguese population and thus reduce their risk.